Poly(acrylonitrile) ultrafiltration membranes. I. polymer-salt-solvent interactions - Phadke, M. A.; Musale, D. A.; Kulkarni, Sudhir S.; Karode, Sandeep K. (Journal of Polymer Science Part B: Polymer Physics, 2005)
Fourier transform infrared spectroscopy was used to study the interactions among LiCl, ZnCl2, and AlCl3 with NN-dimethylformamide (DMF) and poly (acrylonitrile) (PAN). It was observed that all three salts complex with DMF as well as PAN. The strength of the cation interaction with the > C=O oxygen of DMF was found to be higher than that with the -CN group of PAN. The > C=O stretching frequency of DMF with ZnCl2 was red shifted, indicating stronger complex formation compared with other two cations. With the addition of salt, the salt-DMF pseudo solvent was found to become a 0 solvent for PAN compared with neat DMF. This change in PAN solvation power was primarily the result of DMF-salt complexation. As a result of the complexation, Mark-Houwink constant a, was found to reduce from 0.75 (for pure DMF) to similar to 0.6 for DMF-salt solvents, indicating decreased PAN chain expansion. Comparison of intrinsic viscosity [n] values indicated that addition of salts to PAN-DMF solutions resulted in: (i) decrease in the DMF solvation. power, which causes less expanded polymer coils, and (ii) increased interpolymer chain entanglements via salt-promoted chain association. (c) 2005 Wiley Periodicals, Inc.
Keywords: activation energy viscosity; Additives; FT-IR; Poly(acrylonitrile); solution properties